Applying Wordwall.net to Improve Mastery of Automotive Light Vehicle Engineering Vocabularies of Vocational Students - Dina Sabiela Rosyadi (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
English plays a crucial role in vocational education, particularly in preparing students for global work environments. However, students often struggle with mastering technical vocabulary using conventional methods. This study aims to investigate the effectiveness of Wordwall.net as a digital learning tool in enhancing the mastery of technical vocabulary among vocational high school students majoring in Automotive Light Vehicle Engineering. The study employed a quasi-experimental design with two non-equivalent groups. A total of 56 tenth-grade students were selected purposively, with one class receiving Wordwall.net-based instruction and the other using Quizizz. Pre-tests and post-tests were administered to measure vocabulary gains. The results showed a significant improvement in the experimental group's vocabulary scores compared to the control group (p = .014), with a moderate to large effect size (η² = 0.108). These findings suggest that Wordwall.net effectively supports the acquisition of technical vocabulary by providing interactive, engaging, and visually supportive activities. The study concludes that Wordwall.net is a valuable pedagogical tool in vocational language education.